UFLPlus: An Underwater Fish Lamp Technology as an Innovation of Fish-Luring Aids on Boat Lift Net - Fajriah Fajriah; Ahmad Mustafa; Muhammad Rais; La Anadi; Kobajashi Togo Isamu; Marsuki Iswandi; Idrus Salam; Sampunur Sampunur (Jurnal Ilmiah Perikanan dan Kelautan, 2022)
Highlight ResearchDipped lamp technology with CCTV (UFLPlus) to catch fish was designed in such a way that the placement of components contained was integrated, water-proof, and having a good light distribution.The existence of a CCTV in new innovated UFLPlus that can record events in the water and greatly assist fishing activities of fishermen on passive fishing gear such as boat charts.UFLPlus worked well to increase the number of hauling every night of fishing (from 20-30 kg to 50-60 kg per hauling).AbstractThe usage of underwater immersion lights outfitted with CCTV is a technological innovation that is expected to solve the inadequacies of the acoustic work system while also improving the existing underwater immersion light work system. Underwater Fish Lamp Plus (UFLPlus) technology can attract attention and directly monitor the condition of fish in the sea from the boat. The purpose of this study was to understand how the UFLPlus was designed and constructed; to test its performance using lamplight, waterproof, and immersion tests; to learn how the light distribution pattern is formed; and to learn the state of the catch. The study was separated into two phases: the design and fabrication of UFLPlus, and numerous laboratory-scale experiments and outdoor trials with boat lift net fishing gear. The results reveal that UFLPlus performed effectively in the field after all of its physical components were tested in the laboratory, and that the values of light intensity and light distribution patterns are still in accordance with the level of adaptation to light reception on the fish retina. During the trial catch, 62 kg of anchovy (Stolephorus sp.), 27 kg of ponyfishes (Leiognathus sp.), 32.5 kg of fringe-scale sardinella (Sardinella fimbriata), and 17.5 kg of yellow-stripe scad (Selaroides leptolepis) were caught. UFLPlus was capable of functioning as an underwater immersion lamp that attracts fish attention and directly monitors the arrival of fish in the water in the fishing area.